Dampak Bullying Verbal Terhadap Menurunnya Rasa Percaya Diri - Khairur Rahmah; Budi Purwoko (EDUKASIA: Jurnal Pendidikan dan Pembelajaran, 2024)
This research aims to analyze the impact of bullying on students' self-confidence. This research uses a literature review method to collect, identify, evaluate and interpret articles related to the impact of verbal bullying behavior on self-confidence. The data used comes from the results of research that has been conducted and published. Researchers use publish or perish found directly into Google Scholar search to search for relevant journals. The systematic review was carried out using the PRISMA (Preferred international for systematic and metaanalysis) procedure, which consists of identification, screening, eligibility and inclusion. The impact of verbal bullying activities is a decrease in self-confidence. Self-confidence is an attitude in assessing a person's self and their confidence and ability to do something according to their abilities. The characteristics of decreased self-confidence are feeling anxious, low self-esteem, tending to always be silent, and feeling insecure. To overcome bullying, socialization is needed for students to report bullying to teachers and parents, as well as helping to increase students' self-confidence.